Julolidinyl aza-BODIPYs as NIR-II fluorophores for the bioimaging of nanocarriers - Chang Liu; Yifan Cai; Zichen Zhang; Yi Lu; Quangang Zhu; Haisheng He; Zhongjian Chen; Weili Zhao; Wei Wu (Elsevier, 2024)
The aggregation-caused quenching (ACQ) rationale has been employed to improve the fluorescence imaging accuracy of nanocarriers by precluding free probe-derived interferences. However, its usefulness is undermined by limited penetration and low spatiotemporal resolution of NIR-I (700-900 nm) bioimaging owing to absorption and diffraction by biological tissues and tissue-derived autofluorescence. This study aimed to develop ACQ-based NIR-II (1000-1700 nm) probes to further improve the imaging resolution and accuracy. The strategy employed is to install highly planar and electron-rich julolidine into the 3,5-position of aza-BODIPY based on the larger substituent effects. The newly developed probes displayed remarkable photophysical properties, with intense absorption centered at approximately 850 nm and bright emission in the 950-1300 nm region. Compared with the NIR-I counterpart P2, the NIR-II probes demonstrated superior water sensitivity and quenching stability. ACQ1 and ACQ6 exhibited more promising ACQ effects with absolute fluorescence quenching at water fractions above 40% and higher quenching stability with less than 2.0% fluorescence reillumination in plasma after 24 h of incubation. Theoretical calculations verified that molecular planarity is more important than hydrophobicity for ACQ properties. Additionally, in vivo and ex vivo reillumination studies revealed less than 2.5% signal interference from prequenched ACQ1, in contrast to 15% for P2.